(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this article, we can see the philosophical rationalist ideas that began to emerge in ancient Athens. We will get acquainted with the views of scientists who were engaged in philosophy in the early period, the processes of trying to rationally understand the world. In addition, we will learn about the efforts to rationally understand man.